(3eZfi GddHjH Yf cJH GdCYGQjHs - (3YHO Gddg Hf jhSa Hf CMeO GdCfUGQj GdeUQj GdfMhj , LeGd GdOjf , CHh eMeO, GHf gTGe J (B761 (3g` s ((3Ydi Hf YHO Gddg Hf Ydi GdefjQ s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg Ydi CaVGdg aEf Chdi eG JbJQMg GdaQGFM hCYdi eG JMJGL Edi JMUjdg GdLhGfM , s
(3BNQgG (B:s
(3hdh PcQJ CMQa GdLQ hONhd HYVgG Ydi HYV GdeGA Pdc CeKdI cKjQI hgPG BNQ eG JjSQ EjQGOg ai gPG GdJCdja s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdfMhs